Kualitas Karkas Babi Potong yang Dilahirkan dari Induk yang Disuperovulasi Sebelum Pengawinan (CARCASS QUALITIES OF FINISHER PIG BORN TO SUPEROVULATED SOWS BEFORE MATING) - Lapian, Mien Theodora Rossesthellinda; Siagian, Pollung Hasiholan; Manalu, Wasmen; Priyanto, Rudy (Jurnal Veteriner, 2013)
An experiment was conducted to study the effect of superovulation of the sows before mating on thecarcass quality of the finishing piglets.  Forty two gilts were divided into two treatments i.e., 1)nonsuperovulate gilts and 2) superovulate gilts.  At parturition, each group of sows were divided into threelitter size ranges i.e., 6-8 (low), 9-11 (medium), and 12-14 (high), with three replications.  Each replicationwas represented by two offsprings, one male and one female.  Therefore, the total samples were 36 piglets.During growing to finishing periods, the experimental piglets were fed commercial feed.  The experimentalpiglets were slaughtered at average weight of 92,5- 94 kg.  The results showed that piglets born tosuperovulated sows reached the slaughter weight at 185 days as compared to 200 days in control piglets.Piglets born to superovulated sows had higher carcass weight (70,25 ± 2,70 kg) and carcass percentage(74,73 ± 3,09%) as compared to control piglets (64,18 ± 3,58 kg carcass weight and 68,28 ± 3,90% carcasspercentage, respectively).  Carcass length and  backfat thickness were not affected by superovulation.Piglets born to superovulated sows had 74,56 ± 4,72 cm carcass length and 3,07 ± 0.35 cm backfatthickness, while control piglets had 74,00 ± 2,81 cm carcass length and 3.20 ± 0.35 cm backfat thickness.Piglets born to superovulated sows had higher  loin eye area (44,81 ± 3,55 cm²) as compared to control(39,97 ± 4,29 cm²).  It was concluded that superovulation of sows prior to mating could produce fastergrowing piglets with better carcass qualities
Keywords: Superovulation, Carcass Qality, Gilt